CO2 capture by aqueous Na2CO3 integrated with high-quality CaCO3 formation and pure CO2 release at room conditions. (December 2017) - Barzagli, F.; Giorgi, C.; Mani, F.; Peruzzini, M.
Graphical abstract: Highlights: Efficient CO2 capture by diluted aqueous Na2 CO3 at room temperature. CO2 capture and production of high quality CaCO3 . CO2 capture from a flue gas and its release in a pure form at room temperature and pressure. Quantification of carbonate and bicarbonate in solution based on 13 C NMR analysis. Abstract: The absorption of carbon dioxide from anthropogenic emissions and its utilization as a building block for the synthesis of useful chemicals is gaining increasing interest in recent years as an alternative to the conventional CO2 capture and storage (CCS) technologies. The conversion of carbon dioxide into valuable commodities has the advantage of avoiding the energy penalties of absorbent regeneration, CO2 compression and its disposal underground. In this paper we report a novel semi-continuous technique of CO2 capture from a gas mixture by dilute (0.83 mol dm −3 ) aqueous solutions of Na2 CO3 with a sufficiently high absorption efficiency (about 80%) combined with the nearly quantitative production of high quality CaCO3 and CO2 minimizing the energy requirements since the entire process occurred at room conditions. The highly pure CaCO3 and CO2 recovered by the process are valuable products that have the potential of reducing the costs of the CO2 capture process. The 13 C NMR spectroscopy is employed to identify and quantify the species in solution.